Residual hydrocarbons of coal and evaluation of their role in development of fire and explosion emergencies in coal mines - V. S. Lebedev; O. V. Scopinseva; I. E. Stukalova (Известия высших учебных заведений: Геология и разведка)
The paper presents the results of study of the residual hydrocarbons of coal, from brown coals to anthracites. Extraction of the residual hydrocarbons was performed at 200 °С. The dependence of the composition of the hydrocarbons on the stage of coal metamorphism has been defined. The highest content of the residual hydrocarbons (up to 70 cm3/kg) has been defined in coals of middle stages of metamorphism, where heavy hydrocarbons are predominating (heavy hydrocarbon fraction reaches 97 percent relative). In brown coals the content of residual hydrocarbons is low, the heavy hydrocarbons also prevail over СН4 (proportion of heavy hydrocarbons is on average 62 per cent relative). In the coals of higher stages of metamorphism (semi-anthracite and anthracite) the content of residual hydrocarbons is low and СН4 prevails. Residual hydrocarbons might be emitted from the coal during the mining in the shaft air. The role of residual hydrocarbons enriched in heavy hydrocarbons is reviewed in the sense of the development of fire and explosion emergencies in coal mines.